Bernstein in the urban classroom: a case study. Issue 8 (17th November 2017) - Barrett, Brian D.
Abstract: Despite a long-standing concern within the sociology of education for ameliorating educational inequality, the challenge of improving educational opportunities for disadvantaged students remains deeply entrenched. While 'macro' issues such as segregation and systemic inequalities in school funding and access to qualified teachers must be addressed as matters of social and educational justice, Basil Bernstein's novel focus on 'relations within' education as the site of pedagogic discourse offers teachers and those working inside school systems a particularly powerful vision for promoting more equitable outcomes for students. This paper examines this assertion through a case study of the 'mixed' pedagogical practice of a successful teacher in a fifth-grade urban classroom in the United States.